Preparation method of MFI molecular sieve, MFI molecular sieve and application
Through the preparation method of the integrated MFI molecular sieve without binders, the problem of channel blockage caused by binders is solved, the catalytic activity and selectivity of the cyclopentylbenzene reaction is improved, and the efficient gas-phase alkyl of benzene and cyclopentene are achieved. .
Patent Information
- Application Number
- CN202310869127.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-07-14
AI Technical Summary
The existing MFI molecular sieve has pore blockage caused by binders in the gas-phase alkylation reaction of cyclopentylbenzene, which affects the diffusion and selectivity of reactants.
Using the integrated MFI molecular sieve preparation method without binder, hydrothermal crystallization and calcination are carried out by mixing the first silicon source, the second silicon source, the second aluminum source, the template agent and the alkali source to form a regular arrangement of mesoporous structure. MFI molecular sieve avoids the presence of binder.
The catalytic activity and selectivity are improved, the generation of by-products is reduced, and the efficient gas-phase alkylation reaction of benzene and cyclopentene is achieved.
Smart Images

Figure CN119306233A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an MFI molecular sieve, and in particular to an MFI molecular sieve and a preparation method and application thereof. Background Art
[0002] With the rapid development of my country's ethylene industry, the C5 fraction as a by-product of ethylene has grown rapidly. Cyclopentadiene is one of the more abundant components in C5 resources. Cyclopentene is an important basic organic chemical raw material, which is usually used in the pharmaceutical industry, organic synthesis and synthetic rubber. Cyclopentene can be obtained by hydrogenation of cyclopentadiene. The most important derivatives of cyclopentene are cyclopentanone and cyclopentanol. The research on producing cyclopentene with C5 fraction as raw material and then synthesizing cyclopentanone and cyclopentanol has attracted widespread attention.
[0003] Cyclopentylbenzene can be produced by gas phase alkylation of cyclopentene and benzene, and cyclopentanone and phenol can be obtained through oxidation and decomposition steps. Similar to the process of producing phenol and acetone from isopropylbenzene, the process of producing phenol and cyclopentanone from cyclopentylbenzene also has the advantages of high cyclopentene conversion rate and good selectivity of target products.
[0004] The zeolite catalysts usually synthesized are fine powders with particle sizes ranging from a few nanometers to a few microns. Such fine powders must be molded into different forms such as granules and strips together with inorganic binders (clay, alumina, etc.) to meet the application requirements. The presence of binders disperses and dilutes the active components, blocks the pores of the zeolite molecular sieve, hinders the utilization of active sites, affects the diffusion of reactant molecules, and objectively reduces the selectivity of the reaction. Combining zeolite powders into a monolithic catalyst without a binder is an interesting research hotspot. Monolithic catalysts refer to integrated catalysts with many narrow, neatly arranged pores. Compared with traditional molded granular catalysts, monolithic catalysts can improve the efficiency of catalysis, improve the selectivity of the reaction, and help to achieve low energy consumption, low emissions and safe process. Existing monolithic binder-free MFI molecular sieves are used in the gas-phase alkylation reaction of preparing cyclopentylbenzene. Summary of the invention
[0005] In order to overcome the problems existing in the prior art, the present invention provides an integral binder-free MFI molecular sieve. When applied to the gas phase alkylation reaction for preparing cyclopentylbenzene, the specific pore structure is suitable for the gas phase alkylation reaction of benzene and cyclopentene, and has the characteristics of high activity, good selectivity and less by-products in such reactions.
[0006] In one aspect, the present invention provides a method for preparing a monolithic binder-free MFI molecular sieve, comprising the following steps:
[0007] (1) forming and drying a mixture of a first silicon source, a first aluminum source, and a second silicon source to obtain a precursor material containing amorphous silicon dioxide and an aluminum source;
[0008] (2) mixing the precursor material obtained in step (1) with a second aluminum source, a template, an alkali source and water, and then crystallizing to obtain an intermediate crystalline material;
[0009] (3) calcining the intermediate crystalline material obtained in step (2);
[0010] The MFI molecular sieve contains no binder.
[0011] In some embodiments, the molar ratio of the first silicon source to the second silicon source is 1:(0.1-0.4), for example, 1:0.1, 1:0.15, 1:0.20, 1:0.25, 1:0.30, 1:0.35, or 1:0.38, calculated as SiO2.
[0012] In some embodiments, the molar ratio of the first aluminum source to the second aluminum source, calculated as Al2O3, is 1:(0.1-1.2), for example 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1.
[0013] In some embodiments, the molar ratio of the first aluminum source to the second aluminum source is 1:(0.1-0.4) based on Al2O3.
[0014] In some embodiments, the molar ratio of the first silicon source calculated as SiO2 to the first aluminum source calculated as Al2O3 is 1:(0.05-1.4), for example, 1:0.1, 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, 1:0.45, 1:0.5, 1:0.55, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, and 1:1.3.
[0015] In some embodiments, the molar ratio of the first silicon source calculated as SiO2 to the first aluminum source calculated as Al2O3 is 1:(0.1-0.5).
[0016] In some embodiments, the molar ratio of the second silicon source calculated as SiO2 to the second aluminum source calculated as Al2O3 is 1:(0.05-0.6).
[0017] In some embodiments, the molar ratio of the second silicon source calculated as SiO2 to the second aluminum source calculated as Al2O3 is 1:(0.1-0.6), for example, 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, 1:0.45, 1:0.5, or 1:0.55.
[0018] In some embodiments, the molar ratio of the second silicon source calculated as SiO2 to the second aluminum source calculated as Al2O3 is 1:(0.1-0.3).
[0019] In some embodiments, the molar ratio of the total silicon source calculated as SiO2 to the second aluminum source calculated as Al2O3 is 1:(0.01-0.08), for example, 1:0.01, 1:0.015, 1:0.02, 1:0.025, 1:0.03, 1:0.035, 1:0.04, 1:0.045, 1:0.05, 1:0.065, or 1:0.07.
[0020] In some embodiments, the molar ratio of the total silicon source calculated as SiO2 to the second aluminum source calculated as Al2O3 is 1:(0.02-0.067).
[0021] In some embodiments, the molar ratio of the total silicon source calculated as SiO2 to the template is 1:(0.1-0.8), for example 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7.
[0022] In some embodiments, the molar ratio of the total silicon source in terms of SiO2 to the alkali source is 1:(0.04-0.2), for example, 1:0.05, 1:0.08, 1:0.1, 1:0.13, 1:0.15, 1:0.17, 1:0.20. In some embodiments, the molar ratio of the total silicon source in terms of SiO2 to the alkali source is 1:(0.05-0.15).
[0023] In some embodiments, the molar ratio of the total silicon source, calculated as SiO2, to water is 1:(5-35), for example, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19, 1:20, 1:21, 1:22, 1:23, 1:24, 1:23, 1:25, 1:27, 1:29, 1:32.
[0024] In some embodiments, the molar ratio of the total silicon source calculated as SiO2 to water is 1:(10-30).
[0025] In some embodiments, the drying temperature is 80-200° C., such as 100° C., 120° C., 130° C., 140° C., 150° C., 160° C. or 170° C. In some embodiments, the drying temperature is 100-150° C.
[0026] In some embodiments, the drying time is 2 to 24 hours, preferably 3 to 10 hours.
[0027] In some embodiments, the calcination temperature is 450-1000° C., such as 480° C., 500° C., 520° C., 550° C., 580° C., 600° C., 650° C., 700° C., 720° C., 750° C., 800° C. In some embodiments, the calcination temperature is 500-750° C.
[0028] In some embodiments, the calcination time is 1 to 12 hours, such as 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours. In some embodiments, the calcination time is 2 to 10 hours.
[0029] In some embodiments, the crystallization temperature is 140-220° C., such as 140° C., 150° C., 160° C., 170° C., 180° C., 190° C. or 200° C. In some embodiments, the crystallization temperature is 150-200° C.
[0030] In some embodiments, the crystallization time is 12 to 110 hours, such as 12 hours, 14 hours, 18 hours, 20 hours, 24 hours, 28 hours, 30 hours, 40 hours, 48 hours, 50 hours, 56 hours, 60 hours, 64 hours, 70 hours, 72 hours, 76 hours, 80 hours, 85 hours, 90 hours, 95 hours, 100 hours or 110 hours. In some embodiments, the crystallization time is 24 to 100 hours.
[0031] In some embodiments, the first silicon source includes one or more of solid silicon dioxide, silica gel, white carbon black, or silicon dioxide aerosol.
[0032] In some embodiments, the first aluminum source includes one or more of aluminum hydroxide, sodium aluminate, aluminum isopropoxide, aluminum nitrate, anhydrous aluminum chloride, aluminum sulfate, kaolin, or montmorillonite.
[0033] In some embodiments, the second aluminum source includes one or more of aluminum hydroxide, sodium metaaluminate, aluminum isopropoxide, aluminum nitrate, anhydrous aluminum chloride, or aluminum sulfate.
[0034] In some embodiments, the second silicon source is silica sol. In some embodiments, the second silicon source is 10-50 wt % silica sol. In some embodiments, the second silicon source is 35-45 wt % silica sol.
[0035] In some embodiments, the templating agent comprises an organic amine templating agent.
[0036] In some embodiments, the organic amine template includes one or more of tetrapropylammonium bromide, dimethylamine, trimethylamine, ethylenediamine, hexyldiamine, cyclohexylamine, isopropylamine, diethylamine, triethylamine or n-butylamine.
[0037] In some embodiments, the organic amine template includes one or more of tetrapropylammonium bromide, isopropylamine, cyclohexylamine, hexamethylenediamine, ethylenediamine, diethylamine, n-butylamine, and triethylamine.
[0038] In some embodiments, the alkali source comprises an alkali metal hydroxide; preferably, the alkali source is NaOH or KOH.
[0039] On the other hand, the present invention provides a monolithic binder-free MFI molecular sieve, wherein:
[0040] The molecular sieve has micropores and mesopores, wherein the micropores are pores with a pore diameter less than 2 nm, and the mesopores are pores with a pore diameter of 2 to 50 nm, and the mesopores account for more than 56% of the total pore volume.
[0041] In some embodiments, the mesopores account for 56% to 86% of the total pore volume, such as 56%, 60%, 62%, 65%, 68%, 70%, 72%, 75%, 78%, 80%, 83% or 86%. In some embodiments, the mesopores account for 65% to 85% of the total pore volume. In some embodiments, the mesopores account for 70% to 80% of the total pore volume.
[0042] In some embodiments, the mesopore includes a first mesopore, a second mesopore and a third mesopore, the pore size d1 of the first mesopore satisfies: 2.0nm<d1≤5.0nm, the pore size d2 of the second mesopore satisfies: 5.0nm<d2≤20nm, and the pore size d3 of the third mesopore satisfies: 20nm<d3<50nm.
[0043] In some embodiments, the pore volume of the first mesopores accounts for 30% to 50% of the total pore volume, preferably 30% to 45%, such as 32%, 35%, 38%, 40%, 42% or 45%.
[0044] In some embodiments, the pore volume of the second mesopores accounts for 20% to 33% of the total pore volume, preferably 20% to 30%, such as 22%, 25%, 28% or 30%.
[0045] In some embodiments, the pore volume of the third mesopores accounts for less than 12% of the total pore volume, such as 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or 11%. In some embodiments, the pore volume of the third mesopores accounts for 5% to 11% of the total pore volume. In some embodiments, the pore volume of the third mesopores accounts for 6% to 11% of the total pore volume.
[0046] In some embodiments, the acid amount of the molecular sieve is 0.9 to 2 mmol / g, for example, 0.95 mmol / g, 0.98 mmol / g, 1.00 mmol / g, 1.05 mmol / g, 1.10 mmol / g, 1.15 mmol / g, 1.25 mmol / g, 1.35 mmol / g, 1.45 mmol / g or 1.5 mmol / g.
[0047] In some embodiments, the molecular sieve has a specific surface area of 400 to 600 m 2 / g, for example 400m 2 / g, 420m 2 / g, 450m 2 / g, 480m 2 / g、500m 2 / g, 520m 2 / g, 540m 2 / g, 550m 2 / g, 560m 2 / g or 580m 2 / g.
[0048] In some embodiments, the average pore size of the molecular sieve is 2.5 nm to 5.5 nm. In some embodiments, the average pore size of the molecular sieve is 3 to 4.7 nm. In some embodiments, the average pore size of the molecular sieve is 3.2 to 4.5 nm.
[0049] In some embodiments, the total pore volume of the molecular sieve is 0.3 to 0.8 cm 3 / g, for example 0.35cm 3 / g, 0.4cm 3 / g, 0.45cm 3 / g, 0.5cm 3 / g, 0.55cm 3 / g, 0.6cm 3 / g, 0.65cm 3 / g, 0.7cm 3 / g, 0.75cm 3In some embodiments, the total pore volume of the molecular sieve is 0.4 to 0.7 cm 3 / g.
[0050] In some embodiments, the micropore volume of the molecular sieve is 0.1 to 0.5 cm 3 / g, for example 0.1cm 3 / g, 0.2cm 3 / g, 0.22cm 3 / g, 0.25cm 3 / g, 0.3cm 3 / g, 0.35cm 3 / g, 0.38cm 3 / g, 0.4cm 3 / g or 0.45cm 3 / g.
[0051] In some embodiments, the molecular sieve has one or more of the following features (a) to (h):
[0052] (a) The acid content of the molecular sieve is 0.9 to 2 mmol / g, preferably 1 to 1.5 mmol / g;
[0053] (b) The specific surface area of the molecular sieve is 400 to 600 m 2 / g;
[0054] (c) The average pore size of the molecular sieve is 2.5 nm to 5.5 nm, preferably 3 nm to 4.7 nm; preferably 3.2 nm to 4.5 nm;
[0055] (d) The total pore volume of the molecular sieve is 0.3 to 0.8 cm 3 / g, preferably 0.35 to 0.75 cm 3 / g; preferably 0.4 to 0.7 cm 3 / g;
[0056] (e) The micropore volume of the molecular sieve is 0.1 to 0.5 cm 3 / g, preferably 0.22 to 0.45 cm 3 / g;
[0057] (f) the pore volume of the first mesopores accounts for 30% to 50% of the total pore volume, preferably 30% to 45%, the pore volume of the second mesopores accounts for 20% to 33% of the total pore volume, preferably 20% to 30%, and the pore volume of the third mesopores accounts for less than 12% of the total pore volume, preferably 6-11%;
[0058] (g) The molecular sieve has a closed hysteresis loop at P / P0=0.4-0.99 on the nitrogen adsorption-desorption curve. Preferably, the starting position of the closed hysteresis loop is at P / P0=0.4-0.7; the difference between the absorption mass of the adsorption curve and the desorption curve is 0-6cm 2 / g;
[0059] (h) The molecular sieve X-ray diffraction (XRD) spectrum has characteristic peaks at 2θ angles of 8.0°±0.25° and 9.0±0.4°, preferably, has characteristic peaks at 8.0°±0.20° and 9.0±0.35°.
[0060] On the other hand, the present invention provides use of a monolithic binderless MFI molecular sieve or a monolithic binderless MFI molecular sieve prepared by the preparation method of the present invention as a catalyst in the production of cyclopentylbenzene.
[0061] Preferably, the raw material for producing cyclopentylbenzene contains benzene and cyclopentene.
[0062] On the other hand, the present invention provides a method for producing cyclopentylbenzene, wherein benzene and cyclopentene are used as raw materials, and the raw materials are contacted with a catalyst to react to synthesize cyclopentylbenzene, and the catalyst is the integral binderless MFI molecular sieve described in the present invention or the integral binderless MFI molecular sieve prepared by the preparation method described in the present invention.
[0063] In some embodiments, the molar ratio of benzene to cyclopentene is (1-5):1; preferably, the molar ratio of benzene to cyclopentene is (1-3):1.
[0064] In some embodiments, the reaction temperature of the reaction is 150-300°C, the reaction pressure is 0.8-1.5 MPa, and the weight space velocity of cyclopentene is 0.05-2h -1 Preferably, the reaction temperature is 150-250°C, the reaction pressure is 0.9-1.2MPa, for example 1Mpa, and the weight space velocity of cyclopentene is 0.05-1h -1 .
[0065] The integral binder-free MFI molecular sieve provided by the present invention is used as a catalyst, has a large specific surface area and a high acid content. When benzene and cyclopentene are used as raw materials to produce cyclopentylbenzene, the specific pore structure is suitable for the gas phase alkylation reaction of benzene and cyclopentene, and has the characteristics of high activity, good selectivity and less by-products in this type of reaction.
[0066] The preparation method of the monolithic binder-free MFI molecular sieve described in the present invention is a special process, which first uses a silicon source and a first aluminum source to form a strip with silica sol and then dry it, and then uses a second aluminum source, an alkali source, a template and water to undergo liquid phase hydrothermal crystallization, and then performs a calcination technical solution. The preparation method of the monolithic binder-free MFI molecular sieve described in the present invention utilizes the characteristics of the weak guiding ability of the small molecule organic amine template agent in the crystallization process of the molecular sieve, so that the precursor containing the amorphous silica material and the aluminum source material mixed is converted into a monolithic binder-free MFI molecular sieve in situ. Due to the interface shrinkage effect during the crystallization process, many regularly arranged mesopores are generated. The monolithic binder-free MFI molecular sieve described in the present invention has both a regular mesoporous structure and a pore structure and morphological characteristics unique to the MFI molecular sieve. The above-mentioned specific structural characteristics make the molecular sieve have the advantages of good catalytic activity, faster material diffusion rate, and more stable catalyst performance when used in the reaction of catalyzing the gas-phase alkylation of benzene and cyclopentene. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] The accompanying drawings are used to provide further understanding of the present application and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present application, but do not constitute a limitation to the present application.
[0068] Figure 1 This is the XRD spectrum of the monolithic binder-free MFI molecular sieve prepared in Example 1 of the present invention.
[0069] Figure 2 This is the N2 adsorption-desorption curve of the monolithic binder-free MFI molecular sieve prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0070] In order to make the purpose, technical scheme and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with the embodiments and drawings. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion.
[0071] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0072] In this article, "n~m units" and "n unit~m unit" have the same meaning, wherein n and m are numerical values, and the unit is the unit of the numerical value, such as 450~1000℃ and 450℃~1000℃ have the same meaning, indicating a range of 450℃ to 1000℃.
[0073] The extrusion aid may be one or more of sesbania powder, methyl cellulose, ethyl cellulose, graphite, starch, polyvinyl alcohol and polyacrylamide. In some embodiments of the present invention, the extrusion aid used is sesbania powder.
[0074] The present invention uses the following equipment to characterize the prepared monolithic binder-free MFI molecular sieve, and the following examples all use the same characterization equipment and testing methods.
[0075] In the present invention, a Japanese Rigaku-Ultima X-ray diffractometer is used to analyze the molecular sieve crystal phase. The XRD test conditions are: CuKα radiation, wavelength λ=0.15432nm; X-ray diffraction pattern scanning range 2θ=5°~50°, scanning speed 10° / min, working voltage 40kV, current 40mA.
[0076] In the present invention, N2 physical adsorption is used to determine the average pores and total pore volume of the molecular sieve, and the test method is as follows: the specific surface area (BET) and pore volume of the sample are analyzed using the Autosorb-I automatic adsorption specific surface and porosity analyzer produced by Quantachrome Company of the United States, wherein the cold trap is liquid nitrogen and the adsorption medium is high-purity nitrogen; the adsorption isotherm equation of the HK model is used to analyze the low-pressure section of the adsorption isotherm to obtain the pore size distribution curve of the molecular sieve; the specific surface area and pore volume of the molecular sieve are calculated respectively by the BET method and the t-plot method.
[0077] In the present invention, the product is analyzed by gas chromatography, a certain amount of the reaction mixture is sampled from the gas chromatograph injection port, and after passing through the chromatographic column, it is detected by FID and quantitatively analyzed by external standard method. The gas chromatograph used is a 7890 gas chromatograph produced by Agilent, and the analytical chromatographic column used is an INNOWAX column.
[0078] The calculation formulas for conversion rate and selectivity in the application examples of the present invention are as follows:
[0079] Cyclopentene conversion rate X HPE = mass percentage of each chromatographic product and by-product / (mass percentage of each chromatographic product and by-product + mass percentage of cyclopentene) × 100%.
[0080] The selectivity of cyclopentylbenzene HPB =Mass percentage of cyclopentylbenzene / (mass percentage of each chromatographic product and by-product)×100%.
[0081] The method for determining the amount of molecular sieve acid in the application example of the present invention is as follows:
[0082] Weigh 0.5 g of molecular sieve powder, add 100 ml of water, stir for 10 minutes, add 0.2 g of piperidine, stir for 30 minutes, add 2 drops of phenolphthalein, and titrate with a 0.2 mol / L potassium hydrogen phthalate aqueous solution until the phenolphthalein changes color. Calculate the volume of potassium hydrogen phthalate aqueous solution used for titration and calculate the acid amount of the molecular sieve in millimoles / gram. The calculation formula is as follows:
[0083] Molecular sieve acid amount=(weight of piperidine / 85.15-concentration of potassium hydrogen phthalate×volume of potassium hydrogen phthalate / 1000) / weight of molecular sieve×1000.
[0084] Examples and drawings are provided below to help understand the present invention. However, it should be understood that these examples and drawings are only used to illustrate the present invention, but do not constitute any limitation. The actual protection scope of the present invention is set forth in the claims. It should be understood that any modifications and changes can be made without departing from the spirit of the present invention.
[0085] Example
[0086] Examples 1-10 were prepared using the following method:
[0087] 1) Mix the first silicon source and the first aluminum source, add an appropriate amount of sesbania powder, an extrusion aid, to the second silicon source to form a strip with a diameter of 1 mm and a length of 0.5 cm. Dry the strip at a certain temperature for a certain time to obtain a precursor silicon material.
[0088] 2) A certain mass of the second aluminum source, template, alkali source and H2O are dissolved and mixed; the precursor silicon material is added to the mixture. Crystallization is carried out at a certain temperature for a certain time to obtain an intermediate crystalline material. The intermediate crystalline material is taken out from the liquid, washed with deionized water, dried, and calcined in a muffle furnace at a certain temperature for a certain time to obtain a monolithic binder-free MFI molecular sieve.
[0089] The reaction conditions of each embodiment are shown in Table 1, and the reaction materials and amounts are shown in Table 2:
[0090] Table 1: Reaction conditions
[0091] Example Drying temperature Drying time Crystallization temperature Crystallization time Calcination temperature Roasting time 1 120℃ 3 hours 180℃ 48 hours 550℃ 5 hours 2 100℃ 10 hours 150℃ 72 hours 500℃ 10 hours 3 130℃ 5 hours 160℃ 100 hours 750℃ 2 hours 4 150℃ 3 hours 200℃ 24 hours 650℃ 8 hours 5 140℃ 4 hours 175℃ 48 hours 700℃ 3 hours 6 110℃ 8 hours 160℃ 72 hours 600℃ 4 hours 7 120℃ 5 hours 170℃ 36 hours 680℃ 4.5 hours 8 135℃ 7 hours 165℃ 70 hours 720℃ 3 hours 9 125℃ 9 hours 190℃ 36 hours 700℃ 6 hours 10 130℃ 6 hours 160℃ 55 hours 580℃ 9 hours
[0092] Table 2: Reaction materials
[0093]
[0094]
[0095] Table 2 continued
[0096]
[0097]
[0098] Parameter test results of Examples 1-10:
[0099] Example 1: XRD characterization results of molecular sieves are as follows Figure 1 The N2 physical adsorption characterization results are shown in Figure 2 As shown. Figure 1 It can be seen that the molecular sieve is a typical MFI molecular sieve. Figure 2 The hysteresis loop was observed, which confirmed the existence of mesopores. The pore volume with a pore size less than 2.0 nm accounted for 25% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 38% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 29% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 8% of the total pore volume. The average pore diameter is 3.9 nm, and the total pore volume is 0.55 cm 3 / g, micropore volume is 0.31cm 3 / g, specific surface area is 520m 2 / g. The acid content of the molecular sieve is 1.28 mmol / g.
[0100] Example 2: Characterization results of N2 physical adsorption of molecular sieves. Hysteresis loops were observed, which confirmed the presence of mesopores. The pore volume with a pore size of less than 2.0 nm accounted for 20% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 45% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 29% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 6% of the total pore volume. The average pore diameter was 3.6 nm, and the total pore volume was 0.46 cm 3 / g, micropore volume is 0.26cm 3 / g, specific surface area is 402m 2 / g. The acid content of the molecular sieve is 1.17 mmol / g.
[0101] Example 3: Characterization results of molecular sieve N2 physical adsorption. Hysteresis loops were observed, which confirmed the presence of mesopores. The pore volume with a pore size less than 2.0 nm accounted for 29% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 44% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 20% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 7% of the total pore volume. The average pore diameter was 3.7 nm, and the total pore volume was 0.40 cm 3 / g, micropore volume is 0.22cm3 / g, specific surface area is 423m 2 / g. The acid content of the molecular sieve is 1.41 mmol / g.
[0102] Example 4: Characterization results of molecular sieve N2 physical adsorption. Hysteresis loops were observed, which confirmed the presence of mesopores. The pore volume with a pore size less than 2.0 nm accounted for 23% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 40% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 28% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 7% of the total pore volume. The average pore diameter was 4.3 nm, and the total pore volume was 0.51 cm 3 / g, micropore volume is 0.38cm 3 / g, specific surface area is 543m 2 / g. The acid content of the molecular sieve is 1.38 mmol / g.
[0103] Example 5: Characterization results of molecular sieve N2 physical adsorption. Hysteresis loops were observed, which confirmed the presence of mesopores. The pore volume with a pore size less than 2.0 nm accounted for 15% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 45% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 30% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 10% of the total pore volume. The average pore diameter was 4.0 nm, and the total pore volume was 0.63 cm 3 / g, micropore volume is 0.42cm 3 / g, specific surface area is 468m 2 / g. The acid content of the molecular sieve is 1.50 mmol / g.
[0104] Example 6: Characterization results of N2 physical adsorption of molecular sieves. Hysteresis loops were observed, which confirmed the presence of mesopores. The pore volume with a pore size less than 2.0 nm accounted for 30% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 43% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 20% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 9% of the total pore volume. The average pore diameter was 4.5 nm, and the total pore volume was 0.55 cm 3 / g, micropore volume is 0.37cm 3 / g, specific surface area is 487m 2 / g. The acid content of the molecular sieve is 1.22 mmol / g.
[0105] Example 7: Characterization results of molecular sieve N2 physical adsorption. Hysteresis loops were observed, which confirmed the presence of mesopores. The pore volume with a pore size less than 2.0 nm accounted for 28% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 32% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 29% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 11% of the total pore volume. The average pore diameter was 4.1 nm, and the total pore volume was 0.70 cm 3 / g, micropore volume is 0.45cm 3 / g, specific surface area is 570m 2 / g. The acid content of the molecular sieve is 1.02 mmol / g.
[0106] Example 8: Characterization results of molecular sieve N2 physical adsorption. Hysteresis loops were observed, which confirmed the presence of mesopores. The pore volume with a pore size less than 2.0 nm accounted for 30% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 30% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 29% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 11% of the total pore volume. The average pore diameter was 3.3 nm, and the total pore volume was 0.67 cm 3 / g, micropore volume is 0.43cm 3 / g, specific surface area is 600m 2 / g. The acid content of the molecular sieve is 1.14 mmol / g.
[0107] Example 9: Characterization results of molecular sieve N2 physical adsorption. Hysteresis loops were observed, which confirmed the presence of mesopores. The pore volume with a pore size less than 2.0 nm accounted for 28% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 34% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 30% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 8% of the total pore volume. The average pore diameter was 3.2 nm, and the total pore volume was 0.49 cm 3 / g, micropore volume is 0.29cm 3 / g, specific surface area is 540m 2 / g. The acid content of the molecular sieve is 1.29 mmol / g.
[0108] Example 10: Characterization results of molecular sieve N2 physical adsorption. Hysteresis loops were observed, which confirmed the presence of mesopores. The pore volume with a pore size less than 2.0 nm accounted for 24% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 43% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 25% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 8% of the total pore volume. The average pore diameter was 3.8 nm, and the total pore volume was 0.59 cm 3 / g, micropore volume is 0.34cm 3 / g, specific surface area is 571m 2 / g. The acid content of the molecular sieve is 1.35 mmol / g.
[0109] Application Method
[0110] 5 g of the prepared monolithic binder-free MFI molecular sieve was loaded into a fixed bed reactor, and a mixture of benzene and cyclopentene was introduced. The reaction temperature was 180°C, the reaction pressure was 1.0 MPa, and the space velocity of cyclopentene was 0.05 h -1 , the molar ratio of benzene to cyclopentene is 1.5:1. The reaction results of Examples 1-10 are shown in Table 3:
[0111] Table 3: Example reaction results
[0112] Example The conversion rate of cyclopentene Selectivity of cyclopentylbenzene 1 95.5% 92.3% 2 98% 94.7% 3 100% 91.4% 4 99.2% 92.6% 5 97% 94.5% 6 94.3% 95.6% 7 98.7% 91.5% 8 90.8% 90.3% 9 92.9% 93.7% 10 96.4% 90.6%
[0113] Example 1A to Example 1E
[0114] Except that the molar ratio of the total silicon source calculated as SiO2 and the second aluminum source calculated as Al2O3, the molar ratio of the alkali source and the molar ratio of water are different from those in Example 1, see Table 4, the other reaction conditions and reaction materials are the same as those in Example 1.
[0115] Catalyst parameter test results:
[0116] Example 1A: No hysteresis loop was observed. The pore volume with a pore size of less than 2.0 nm accounted for 33% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 49% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 15% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 3% of the total pore volume. The average pore diameter was 2.3 nm, and the total pore volume was 0.32 cm 3 / g, micropore volume is 0.21cm 3 / g, specific surface area is 402m 2 / g. The acid content of the molecular sieve is 0.93 mmol / g.
[0117] Example 1B: No hysteresis loop was observed. The pore volume with a pore size of less than 2.0 nm accounted for 35% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 46% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 14% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 5% of the total pore volume. The average pore diameter was 2.1 nm, and the total pore volume was 0.25 cm 3 / g, micropore volume is 0.13cm 3 / g, specific surface area is 375m 2 / g. The acid content of the molecular sieve is 0.87 mmol / g.
[0118] Example 1C: No hysteresis loop was observed. The pore volume with a pore size of less than 2.0 nm accounted for 31% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 47% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 17% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 5% of the total pore volume. The average pore diameter was 2.8 nm, and the total pore volume was 0.25 cm 3 / g, micropore volume is 0.12cm 3 / g, specific surface area is 386m 2 / g. The acid content of the molecular sieve is 0.98 mmol / g.
[0119] Example 1D: No hysteresis loop was observed. The pore volume with a pore size of less than 2.0 nm accounted for 35% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 46% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 14% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 5% of the total pore volume. The average pore diameter was 2.3 nm, and the total pore volume was 0.25 cm 3 / g, micropore volume is 0.14cm 3 / g, specific surface area is 364m 2 / g. The acid content of the molecular sieve is 0.94 mmol / g.
[0120] Example 1E: No hysteresis loop was observed. The pore volume with a pore size of less than 2.0 nm accounted for 25% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 48% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 22% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 5% of the total pore volume. The average pore diameter was 2.4 nm, and the total pore volume was 0.26 cm 3 / g, micropore volume is 0.11cm 3 / g, specific surface area is 367m 2 / g. The acid content of the molecular sieve is 0.87 mmol / g.
[0121] Reaction results: The same application method as in Example 1 was used. The reaction results are shown in Table 4:
[0122] Table 4: Reaction results
[0123]
[0124] Comparative Example 1
[0125] 28.94g of 40% silica sol and a certain amount of aluminum sulfate, triethylamine, NaOH, and H2O are dissolved and mixed. The molar ratio of SiO2, Al2O3, triethylamine, NaOH, and water in the mixture is 1:0.025:0.50:0.10:25. Crystallize at 180°C for 48 hours to obtain the original molecular sieve powder. The original powder is filtered, washed with deionized water, and dried. The obtained powder is formed into strips with a diameter of 1 mm and a length of 0.5 cm by adding a proper amount of extrusion aid with pseudo-boehmite and 5% dilute nitric acid. The mass ratio of the original powder to alumina is 6.5:3.5. The above-formed strips are dried at 120°C for 3 hours. The dried strips are calcined at 550°C in a muffle furnace for 5 hours to obtain the MFI molecular sieve synthesized by the traditional method and formed with a binder.
[0126] Parameter test results:
[0127] Similarly to the test method of the above embodiment, no hysteresis loop was observed, and the average pore diameter of the molecular sieve was 2.3 nanometers, and the total pore volume was 0.24 cm 3 g -1 , the micropore volume is 0.16cm 3 g -1 The pore volume with a pore size less than 2.0 nm accounts for 32% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounts for 47% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounts for 18% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounts for less than 3% of the total pore volume. The specific surface area of the MFI molecular sieve is 279 cm 2 / g. The acid content of the molecular sieve is 1.10 mmol / g.
[0128] Reaction results:
[0129] The same application method as in Example 1 was used. The conversion rate of cyclopentene was 88.1%, and the selectivity of cyclopentylbenzene was 79.6%.
[0130] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing an MFI molecular sieve, comprising the following steps: (1) forming and drying a mixture of a first silicon source, a first aluminum source, and a second silicon source to obtain a precursor material containing amorphous silicon dioxide and an aluminum source; (2) mixing the precursor material obtained in step (1) with a second aluminum source, a template, an alkali source and water, and then crystallizing to obtain an intermediate crystalline material; (3) calcining the intermediate crystalline material obtained in step (2); The MFI molecular sieve contains no binder.
2. The preparation method according to claim 1, characterized in that: Calculated in terms of SiO2, the molar ratio of the first silicon source to the second silicon source is 1:(0.1-0.4); and / or, The molar ratio of the first aluminum source to the second aluminum source is 1:(0.1-1.2), preferably 1:(0.1-0.4), calculated as Al2O3; and / or The molar ratio of the first silicon source calculated as SiO2 to the first aluminum source calculated as Al2O3 is 1:(0.05-1.4), preferably 1:(0.1-0.5); and / or, The molar ratio of the second silicon source calculated as SiO2 to the second aluminum source calculated as Al2O3 is 1:(0.1-0.6), preferably 1:(0.1-0.3); and / or, The molar ratio of the total silicon source calculated as SiO2 to the second aluminum source calculated as Al2O3 is 1:(0.01-0.08), preferably 1:(0.02-0.067); and / or The molar ratio of the total silicon source, calculated as SiO2, to the template is 1:(0.1-0.8); and / or The molar ratio of the total silicon source, calculated as SiO2, to the alkali source is 1:(0.04-0.2), preferably 1:(0.05-0.15); and / or The molar ratio of the total silicon source calculated as SiO2 to water is 1:(5-35), preferably 1:(10-30).
3. The preparation method according to claim 1 or 2, characterized in that: The drying temperature is 80 to 200° C., preferably 100 to 150° C.; the drying time is 2 to 24 hours, preferably 3 to 10 hours; and / or The calcination temperature is 450-1000° C., preferably 500-750° C.; and / or The calcination time is 1 to 12 hours, preferably 2 to 10 hours; and / or The crystallization temperature is 140-220°C, preferably 150-200°C; and / or The crystallization time is 12 to 110 hours, preferably 24 to 100 hours.
4. The preparation method according to any one of claims 1 to 3, characterized in that The first silicon source comprises one or more of solid silicon dioxide, silica gel, white carbon black or silicon dioxide aerosol; and / or The first aluminum source comprises one or more of aluminum hydroxide, sodium aluminate, aluminum isopropoxide, aluminum nitrate, anhydrous aluminum chloride, aluminum sulfate, kaolin or montmorillonite; and / or The second aluminum source includes one or more of aluminum hydroxide, sodium metaaluminate, aluminum isopropoxide, aluminum nitrate, anhydrous aluminum chloride or aluminum sulfate; and / or The second silicon source is silica sol; preferably 10-50wt% silica sol; and / or The template agent includes an organic amine template agent; preferably, the organic amine template agent includes one or more of tetrapropylammonium bromide, dimethylamine, trimethylamine, ethylenediamine, hexyldiamine, cyclohexylamine, isopropylamine, diethylamine, triethylamine or n-butylamine; preferably, the organic amine template agent includes one or more of tetrapropylammonium bromide, isopropylamine, cyclohexylamine, hexyldiamine, ethylenediamine, diethylamine, n-butylamine or triethylamine; and / or The alkali source includes alkali metal hydroxide; preferably, the alkali source is NaOH or KOH.
5. A monolithic binder-free MFI molecular sieve, wherein: The molecular sieve has micropores and mesopores, wherein the micropores are pores with a pore diameter less than 2 nm, and the mesopores are pores with a pore diameter of 2 to 50 nm, and the mesopores account for more than 56% of the total pore volume; Preferably, the mesopores include first mesopores, second mesopores and third mesopores, the pore size d1 of the first mesopores satisfies: 2.0nm<d1≤5.0nm, the pore size d2 of the second mesopores satisfies: 5.0nm<d2≤20nm, and the pore size d3 of the third mesopores satisfies: 20nm<d3<50nm.
6. The MFI molecular sieve according to claim 5, characterized in that The molecular sieve has one or more of the following characteristics (a) to (h): (a) The acid amount of the molecular sieve is 0.9 to 2 mmol / g, preferably 1 to 1.5 mmol / g; (b) The specific surface area of the molecular sieve is 400 to 600 m 2 / g; (c) The average pore size of the molecular sieve is 2.5 to 5.5 nm, preferably 3 to 4.7 nm; preferably 3.2 to 4.5 nm; (d) The total pore volume of the molecular sieve is 0.3 to 0.8 cm 3 / g, preferably 0.35 to 0.75 cm 3 / g; preferably 0.4 to 0.7 cm 3 / g (e) The micropore volume of the molecular sieve is 0.1 to 0.5 cm 3 / g, preferably 0.22 to 0.45 cm 3 / g; (f) the pore volume of the first mesopores accounts for 30% to 50% of the total pore volume, preferably 30% to 45%, the pore volume of the second mesopores accounts for 20% to 33% of the total pore volume, preferably 20% to 30%, and the pore volume of the third mesopores accounts for less than 12% of the total pore volume, preferably 6-11%; (g) The molecular sieve has a closed hysteresis loop at P / P0=0.4-0.99 on the nitrogen adsorption-desorption curve. Preferably, the starting position of the closed hysteresis loop is at P / P0=0.45-0.99; the absorption mass difference between the adsorption curve and the desorption curve is 0-6cm 2 / g; (h) The molecular sieve X-ray diffraction (XRD) spectrum has characteristic peaks at 2θ angles of 8.0°±0.25° and 9.0±0.4°, preferably, has characteristic peaks at 8.0°±0.20° and 9.0±0.35°.
7. Use of the monolithic binderless MFI molecular sieve prepared by the preparation method according to any one of claims 1 to 4 or the monolithic binderless MFI molecular sieve according to any one of claims 5 to 6 as a catalyst in the production of cyclopentylbenzene, Preferably, the raw material for producing cyclopentylbenzene contains benzene and cyclopentene.
8. A method for producing cyclopentylbenzene, wherein: Benzene and cyclopentene are used as raw materials, and the raw materials are contacted with a catalyst to react to synthesize cyclopentylbenzene. The catalyst is an integral binderless MFI molecular sieve prepared by the preparation method described in any one of claims 1 to 4 or an integral binderless MFI molecular sieve described in any one of claims 5 to 6.
9. The method according to claim 8, characterized in that The molar ratio of benzene to cyclopentene is (1-5):1; preferably, the molar ratio of benzene to cyclopentene is (1-3):
1.
10. The method according to claim 8, characterized in that The reaction temperature of the reaction is 150-300°C, the reaction pressure is 0.8-1.5 MPa, and the weight space velocity of cyclopentene is 0.05-2h -1 Preferably, the reaction temperature is 150-250°C, the reaction pressure is 0.9-1.2 MPa, and the weight space velocity of cyclopentene is 0.05-1h -1 .
Citation Information
Patent Citations
Preparation of zeolite binderless ZSM-5
CN101348262A
Method for preparing ethylene by ethanol dehydration
CN103030488A
Preparation method of binderless ZSM-5 molecular sieve
CN107512729A
Preparation method of binder-free all-silicon MCM-41 molecular sieve adsorbent
CN108940188A
Preparation method of binder-free hierarchical pore ZSM-5 molecular sieve catalyst
CN112246274A